Evolutionary adaptation of the protein folding pathway for secretability. (29th August 2022) - Smets, Dries; Tsirigotaki, Alexandra; Smit, Jochem H; Krishnamurthy, Srinath; Portaliou, Athina G; Vorobieva, Anastassia; Vranken, Wim; Karamanou, Spyridoula; Economou, Anastassios
Abstract: Secretory preproteins of the Sec pathway are targeted post‐translationally and cross cellular membranes through translocases. During cytoplasmic transit, mature domains remain non‐folded for translocase recognition/translocation. After translocation and signal peptide cleavage, mature domains fold to native states in the bacterial periplasm or traffic further. We sought the structural basis for delayed mature domain folding and how signal peptides regulate it. We compared how evolution diversified a periplasmic peptidyl‐prolyl isomerase PpiA mature domain from its structural cytoplasmic PpiB twin. Global and local hydrogen–deuterium exchange mass spectrometry showed that PpiA is a slower folder. We defined at near‐residue resolution hierarchical folding initiated by similar foldons in the twins, at different order and rates. PpiA folding is delayed by less hydrophobic native contacts, frustrated residues and a β‐turn in the earliest foldon and by signal peptide‐mediated disruption of foldon hierarchy. When selected PpiA residues and/or its signal peptide were grafted onto PpiB, they converted it into a slow folder with enhanced in vivo secretion. These structural adaptations in a secretory protein facilitate trafficking. Synopsis: In bacteria, secreted proteins remain in a non‐folded state, which enhances their secretion. This study shows that such delayed folding is achieved by signal peptides and mature domain features that slow down the formation of discrete folding units (foldons) and disrupt the foldon pathway hierarchy. Periplasmic PpiA displays delayed folding compared to its fast‐folding structurally similar cytoplasmic homologue PpiB through a distinct, differently ordered hierarchical foldon pathway. A few grafted residues that affect highly stabilized native contacts can interconvert PpiB/PpiA folding kinetics and subsequent secretability. Signal peptides quickly acquire partial secondary structure, increase flexibility in succeeding regions of the mature domain and disturb initial foldon formation to promote secretion. Abstract : Comparison between a slow‐folding secreted bacterial protein (PpiA) and its fast‐folding cytosolic homologue (PpiB) offers insights into structural features that regulate protein folding.